Kajian Aqidah terhadap Praktik Law of Attraction yang Berkembang di Media Sosial Perspektif Syed Muhammad Naquib al-Attas - Ezalia Purnama Sari; Dimas Sadewa; Muhammad Iqbal Habi; Indawan; Shinta Olivia; Hafizul Husni (CV. ALIM'SPUBLISHING, 2026)
The rapid development of social media has popularized self-improvement trends, notably the Law of Attraction (LoA), which posits that positive thoughts and affirmations can attract desired realities. This phenomenon raises crucial questions regarding its compatibility with Islamic creed (aqidah). This study aims to analyze the practice of LoA on social media, examine it from an Islamic aqidah perspective, and evaluate it through the intellectual framework of Syed Muhammad Naquib al-Attas. Employing a qualitative approach with a library research method, data were collected from the Qur’an, Hadith, al-Attas’s works, and relevant literature, then analyzed using descriptive-critical and content analysis methods. The findings indicate that while motivational aspects of LoA, such as optimism and goal-setting, align with the Islamic concept of ikhtiar (effort), the metaphysical claim that human thoughts or